2019
DOI: 10.1186/s41983-019-0124-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of spinal extension exercise program versus muscle energy technique in treatment of chronic mechanical low back pain

Abstract: Background: Mechanical low back pain (MLBP) is a major cause of illness and disability, especially in people of working age. People with chronic low back pain often experience anger, fear, anxiety, decrease in physical ability, and inadequacy of role fulfillment.Objective: This study aimed to compare the efficacy of extension exercise program versus muscle energy technique in treating patients with chronic mechanical low back pain. Subjects and methods: Forty patients complaining of chronic mechanical low back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…A combination of contractions and stretches might be more effective for producing viscoelastic changes because the forces could produce increased viscoelastic change. Our result supports the study of H. Shaker et al [29] found that muscle energy technique was better in decreasing pain and functional disability in patients with chronic mechanical low back pain. Priyanka Dhargalkar et al [30] concluded that MET has got added beneficial effects for decreasing disability and improving function in patients with chronic nonspecific low back pain along with supervised exercises.…”
Section: Discussionsupporting
confidence: 92%
“…A combination of contractions and stretches might be more effective for producing viscoelastic changes because the forces could produce increased viscoelastic change. Our result supports the study of H. Shaker et al [29] found that muscle energy technique was better in decreasing pain and functional disability in patients with chronic mechanical low back pain. Priyanka Dhargalkar et al [30] concluded that MET has got added beneficial effects for decreasing disability and improving function in patients with chronic nonspecific low back pain along with supervised exercises.…”
Section: Discussionsupporting
confidence: 92%
“…Takasaki et al documented positive changes in the spinal disc, i.e. the resolution of herniation, in patient treated with McKenzie method 14 .…”
Section: Discussionmentioning
confidence: 99%
“…This was a cross-sectional study with a total of 120 participants. [ 12 ] The study population was IT professionals of various IT companies who were selected by a simple random sampling method.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%